Neuroprotective kynurenine metabolite indices are abnormally reduced and positively associated with hippocampal and amygdalar volume in bipolar disorder. (February 2015) - Savitz, Jonathan; Dantzer, Robert; Wurfel, Brent E.; Victor, Teresa A.; Ford, Bart N.; Bodurka, Jerzy; Bellgowan, P.S.F.; Teague, T. Kent; Drevets, Wayne C.
Highlights: We measured serum concentrations of kynurenine metabolites in bipolar disorder (BD). We also measured gray matter volume of the hippocampus and amygdala in BD. The ratio of kynurenic acid (KynA) to quinolinic acid (QA) was reduced in BD. The ratio of KynA/3-hydroxykynurenine was correlated with hippocampal volume in BD. Abnormalities in kynurenine metabolism may impact the structure of the hippocampus. Abstract: Inflammation-related changes in the concentrations of kynurenine-pathway metabolites occur in depression secondary to medical conditions but have not been well characterized in primary bipolar disorder (BD), with contradictory results potentially attributable to the presence or absence of psychosis and/or medication effects. In contrast, reductions in hippocampal and amygdalar volume that theoretically reflect dendritic atrophy occurring in the context of a neurotoxic process are commonly reported in unmedicated BD patients. Here we tested whether the concentrations of putatively neuroprotective (kynurenic acid, KynA) and neurotoxic (3-hydroxy-kynurenine, 3HK and quinolinic acid, QA) kynurenine-pathway metabolites were altered in primary BD and whether these metabolites were associated with hippocampal and amygdalar volume. Twenty-five moderately-to-severely depressed unmedicated subjects and 38 moderately-to-severely depressed medicated subjects who met DSM-IV-TR criteria for BD, as well as 48 healthy controls (HCs) completed a structural MRI scan and provided a blood sample for kynurenine metabolite analysis, performed using high performance liquid chromatography with tandem mass spectrometry. Gray matter volumes were measured with the automated segmentation software, FreeSurfer. A putative neuroprotective index, KynA/QA, was significantly lower in the BD subjects relative to the HCs, a finding that was unrelated to current treatment with medication or a prior history of psychosis. Further, another putative neuroprotective index, KynA/3HK was positively associated with hippocampal volume in the BD group after controlling for age, sex, body mass index (BMI), and intracranial volume (ICV). Kyn/3HK was significantly associated with total amygdalar volume in the BD group, but after controlling for age, sex, BMI, but not ICV, this association was reduced to a trend. In addition, Kyn/3HK was positively associated with amygdalar volume in the HCs although the association was no longer significant after accounting for the effects of age, sex, and BMI. The results raise the possibility that BD-associated abnormalities in kynurenine metabolism may impact the structure of the hippocampus and amygdala, highlighting a pathway through which inflammation may exert neuropathological effects in the context of depression.